2008
DOI: 10.1002/chin.200850057
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Novel Bis‐Thiourea Organocatalyst for the Asymmetric Aza‐Henry Reaction.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…7 Recently, we have found that as little as 2 mol% of a simple nonchiral thiourea can accelerate this reaction while suppressing oligomer formation. 8 Herein, we report on the development of a highly enantioselective version of this reaction using a novel bifunctional thiourea catalyst that was rationally designed for this particular transformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Recently, we have found that as little as 2 mol% of a simple nonchiral thiourea can accelerate this reaction while suppressing oligomer formation. 8 Herein, we report on the development of a highly enantioselective version of this reaction using a novel bifunctional thiourea catalyst that was rationally designed for this particular transformation.…”
mentioning
confidence: 99%
“…All of the reactions in Table 1 produced only small amounts of polymer or oligiomers which can be the exclusive product when substoichiometric amounts of a base is used as catalyst. 8,16 Since catalyst 8 is sluggish for this reaction under neat conditions, 5c it was not surprising to find that it is even more sluggish when a solvent is used (entry 1). To optimize turnover, the reaction of 1-nitropropane and nitrostyrene was investigated with decreasing amounts of the catalyst (R)-9, and as expected, the rate of the reaction decreased with decreasing amounts of the catalyst.…”
mentioning
confidence: 99%